Minimum Wages and Wage Distribution in Thailand: A Quantile Selection Model with Copula - Pherng, Wittawat; Buddhawongsa, Piyaluk; Leurcharusmee, Supanika; Maneejuk, Paravee (UUM Press, 2022)
Minimum wage policies were designed to raise the wages of low-skilled workers. In this study, we use data from the Thai Labor Force Survey (2011-2020) to examine the impact of the minimum wage policy on the wage distribution using a quantile regression model corrected for sample selection with a copula. We find that the minimum wage has the strongest effect on the lowest quantile and the effect decreases toward the higher quantiles. This confirms the effectiveness of the minimum wage policy in raising the wages of low-income individuals. In addition, there is also a spill-over effect on individuals in higher wage quantiles. The effect of the minimum wage estimated by our model is smaller compared to the standard quantile regression. This suggests that without correcting for sampling bias, the estimated effect of the minimum wage leads to an upward bias